1983
DOI: 10.1007/bf00393670
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic gram-negative faecal flora in patients with Crohn's Disease and healthy subjects

Abstract: The anaerobic gram-negative faecal flora of five patients with Crohn's Disease (CD) was identified and compared with that of healthy subjects. For isolation and cultivation of the anaerobic gram-negative rods a non-selective medium was used. There were no significant differences in numbers of Bacteroides and Fusobacterium spp. between patients with CD and healthy subjects. However, the numbers of the "Bacteroides fragilis" group were significantly higher in patients than in controls. The high numbers of the "B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 20 publications
1
52
1
1
Order By: Relevance
“…In Crohn's disease, Enterobacteriaceae were observed significantly more frequently than in healthy patients, while there was no difference between active and quiescent disease [42]. Furthermore, a decrease in fecal concentrations of Bifidobacteria in Crohn's disease and in patients with active pouchitis has been reported [43].…”
Section: Ibd As the Results Of An Aberrant Intestinal Microflora?mentioning
confidence: 93%
“…In Crohn's disease, Enterobacteriaceae were observed significantly more frequently than in healthy patients, while there was no difference between active and quiescent disease [42]. Furthermore, a decrease in fecal concentrations of Bifidobacteria in Crohn's disease and in patients with active pouchitis has been reported [43].…”
Section: Ibd As the Results Of An Aberrant Intestinal Microflora?mentioning
confidence: 93%
“…Ruseler-van Embden & Both-Patoir (1983) observed an increase in predominantly anaerobic flora, especially Bacteroides spp., in active Crohn's disease, whilst Hartley et al (1992) isolated a higher level of Bacteroides spp. from patients with active UC, whether at first onset or upon release, than from patients with inactive disease.…”
Section: Discussionmentioning
confidence: 90%
“…Its Polysaccharide A (PSA) component has been shown to inhibit Helicobacter hepaticus-induced experimental colitis in mice [157] and to directly induce the anti-inflammatory function of Foxp3 + Treg cells by acting on TLR2 [158]. Although early observations suggested a higher abundance of Bacteroides fragilis in IBD patients [159], recent studies found lower levels of this commensal [146,147].…”
Section: The Microbiotamentioning
confidence: 82%